Improved charge transfer through the minimal addition of Pb as a sintering aid to TiO2-based low-temperature dye sensitised solar cell - Khir, Hazim; Pandey, Adarsh Kumar; Saidur, Rahman Md; Muhammad Shakeel, Ahmad; Nasrudin, Abd Rahim; Dewika, M.; Samykano, Mahendran (Elsevier Ltd, 2023)
The poor interparticle connectivity between the nanoparticles architecture of photoanode due to insufficient sintering temperature has been an issue for developing flexible dye sensitised solar cell (DSSC). This issue has led flexible DSSC to yield low conversion efficiency. This research aims to implement lead (Pb) as sintering aid to improve the interparticle connection of the photoanode by using the concept of liquid phase sintering. With low melting point of Pb (327.5 °C), necks were formed at the titanium dioxide (TiO2)–Pb interface that improved the connection and lowered the electronic resistance even at low sintering temperature of 150–250 °C. Morphological studies showed the formation of these necks, while phase analysis indicated the more desirable TiO2 anatase phase was present. Specimens containing 5 wt% Pb in the TiO2 matrix showed the highest efficiency value of 8.73% at 250 °C, which is even higher compared to their high-temperature (450 °C) counterpart by 12.21%. This is due to surface fusion of Pb at a lower temperature, leading to enhanced interparticle contact and reduction in recombination reactions. Further increase in Pb did not improve the conversion efficiency which can be due to high charge trapping sites and layer cracking due to high amounts of Pb in TiO2 matrix.